The Role of Integration of Blockchain Technology and Accounting Information Systems on Corporate Financial Efficiency: Literature Review - Ananta, Yorasakhi; Fitri, Salsabila Dwi; Putra, Heldy Eka (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
The development of digital technology has driven a major transformation in accounting practices, especially through the integration of blockchain technology and accounting information systems (AIS). This literature study aims to examine how the implementation of both technologies contributes to improving the financial efficiency of companies. Using a literature review method of articles published between 2018 and 2025, it was found that blockchain offers high transparency, reliability, and security of financial data, while AIS supports the acceleration of reporting and decision-making processes. The combination of the two has been proven to reduce transaction costs, accelerate internal audits, and improve reporting accuracy. Although its implementation still faces a number of challenges such as initial costs and technological readiness, the long-term benefits obtained make this integration a potential strategy to significantly improve financial efficiency. This study emphasizes the importance of managerial support and organizational readiness in adopting digital transformation as a whole.